PENGARUH DEBT TO EQUITY RATIO (DER) DAN RETURN ON EQUITY (ROE) TERHADAP NILAI PERUSAHAAN (PBV) PADA PT ALAM SUTERA REALTY TBK PERIODE 2013-2023 - Anjani, Fera; Oktrima, Bulan (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of Debt To Equity Ratio and Return On Equity on Company Value at PT Alam Sutera Realty Tbk. The research method used is descriptive quantitative and uses statistical analysis. This research uses secondary data, with the population used being the annual financial report at PT Alam Sutera Realty Tbk for 2013-2023. The sample for this data uses reports of financial position and profit and loss from 2013 to 2023. The results of this research were obtained from descriptive tests, classical assumptions, simple and multiple linear regression, as well as hypothesis testing, as well as coefficient of determination tests. Partially the Debt To Equity Ratio has a significant effect on Company Value with a t-count value of 3.637 > ttable 2.306 with a significant value of 0.007 < 0.05, while for partial Return On Equity results there is no significant effect on Company Value with a t-count value of 2.017 < ttable 2.306 with a significant value of 0.078 > 0.05. The results of simultaneous testing of Debt To Equity Ratio and Return On Equity have a significant influence on company value with significant results of 0.003 < 0.05 and the Fcount value is greater than Ftable (12.662 > 4.46). The results of the coefficient of determination test show that the Adjusted R Square (Adj R2) value is 0.704 or 70%, while the remaining 30% can be explained by other variables that are not in this research model.